COVID-19 Vaccines : A Shot in Arm for the Economy - Hansen, Niels-Jakob (IMF Working Papers; Working Paper ;, 2021)
We quantify the effect of vaccinations on economic activity in the United States using weekly county level data covering the period end-2020 to mid-2021. Causal effects are identified through instrumenting vaccination rates with county-level pharmacy density interacted with state-level vaccine allocations, and by including county and state-time fixed effects to control for unobserved factors. We find that vaccinations are a significant and substantial shot in the arm of the economy. Specifically, an increase of initiated vaccination rates of 1 percentage point increases weekly consumer spending by 0.6 percent and reduces weekly initial unemployment claims by 0.004 percentage points of the 2019 labor force. Vaccinations also increase workrelated mobility. Importantly, we find that the effects vary with county characteristics. Specifically, urban counties and counties with initially worse socioeconomic conditions and lower education levels exhibit larger effects of vaccinations. This way, vaccinations are also a fair shot in the arm for the economy, which highlights that equitable distribution of vaccines is important to reduce inequality. Our results are specific to the United States, but hold important lessons for the expected economic impact of vaccinations in other countries.